Natural disease course modeling of achondroplasia to evaluate the efficacy of recifercept in the absence of a placebo control arm in phase II study - Wenlian Qiao; Martin Boucher; Alison Slade; Vikas K. Dawra (Wiley, 2024)
Abstract While randomized, placebo‐controlled, double‐blinded clinical studies are the gold standard for evaluating the efficacy of investigational drugs, the use of placebo in children with achondroplasia should be limited because it provides no clinical benefit while exhausting study participants' treatment window. Recifercept is an investigational drug for treating children with achondroplasia aged 2-10 years. An alternative efficacy evaluation method, instead of a placebo control arm, was employed in the phase II study. Prior to participating in the phase II study, participants completed a natural history (NH) study. Based on the NH data, a multi‐variate linear mixed effects natural disease course model of three anthropometric end points (standing height, sitting height, and arm span) was developed. The model was validated using published growth charts of children with achondroplasia. Subsequently, the model was used to simulate the natural growth trajectories (without any treatment) of the three anthropometric end points for the individuals enrolled in the phase II study. To quantify the efficacy of recifercept, the simulations were compared with the observations post‐recifercept treatment in the phase II study. For all the tested doses of recifercept, at the individual level, the observations were comparable to the simulations at 6 and 12 months post‐recifercept treatment, suggesting no treatment effect. The results contributed to the decision of terminating recifercept clinical development. This work delivers a framework that could eliminate the need for placebo in clinical trials yet provide sufficient evidence for evaluating the efficacy of an investigational drug.